Prospects of Studying of the Problem of Genology in Modern Literary Criticism. (Eurasian Journal of Philology Science and Education, 2015)
The article considers the problem of genology which is one of the most debatable areas of modern literary criticism. Literature is now trying to characterize the specific features of the artistic consciousness,as manifested in the literature and in the philosophical culture of XXI century as «the era of great change ‘conceptually synthesize these two cultural systems. Genre represents a historically formed contentstructure, it is necessary to see in its subject matter what is dictated by time in its perspective. Investigating genre structure enables to observe what means and ways carry out the «vision and understanding ofreality» in a particular work. The genre objectifies a certain aesthetic conception of reality which reveals its content in the integrity of the» artistic statement».
Keywords: modern literary criticism; genology; genre structure; genre form; genre theory; genre typology